IMPACT OF FARM MECHANIZATION ON LABOUR USE FOR WHEAT CULTIVATION IN NORTHERN BANGLADESH - M. S. Rahman; M. A. Monayem Miah; Moniruzzaman; S. Hossain (Journal of Animal and Plant Sciences, 2011)
The study was conducted in three northern districts of Bangladesh during the period of 2009-10 to find out the effect of mechanization on labour use and profitability in wheat cultivation. The findings revealed that less number of labour per hectare is required to complete the production process by mechanized farm compared to traditional farm. Family labour is mostly affected by the mechanization. Animal power and output have positive effect on labour requirement, while power tiller and input costs have adverse effect on labour requirement for wheat cultivation. The yield of wheat under mechanization (2.65 t/ha) is higher than that of traditional farms (2.57 t/ha). Total variable cost is significantly higher for traditional farms. Gross margin is found to be higher for mechanized farm (Tk. 14,168) compared to traditional farm (Tk. 10,102). High price of power tiller parts is mentioned as a major problem of mechanization in the study areas. The study concludes that mechanization has adverse effects on family labour and more research need to be conducted to develop appropriate technology to increase the production of wheat without substituting labour.
Keywords: Mechanization; labour requirement; profitability; labour type; wheat.